Fasting in the holy month of Ramadan and Lipid profile - Sayed Alireza Mirsane; Shima Shafagh; Nasrin Oraei (Journal of Fasting and Health, 2016)
Ramadan is the ninth month of the Islamic calendar, and is a fasting month .Fasting is one of the islamic obligations. This annual ritual is regarded as one of the Five Pillars of Islam according to hadith of fifth Shia imam.In the other hand, Lipid profile is a type of blood tests and this's very important for body health, Specialy individuals with abnormal range of it. A complete lipid profile involves routine tests such as Total Cholesterol(TC), Triglycerides (TG),high-density lipoprotein (HDL,good cholesterol) and low-density lipoprotein (LDL,bad cholesterol).Our goal is determination of Ramadan fasting efficacy on the Lipid profile. With regards to the present study, it can be concluded that fasting have a good effects on the Lipid profile , according to the above fields. But this subject needs to have multiple studies, so it was advised to conduct more study, in order to obtain the comprehensive and exact results. Finally, Holy month of Ramadan and fasting have a lot miracles in different fields of health ,So fasting is a godliness way that it have multiple remedial effects.